Prevalence and Predictors of Antimicrobial Resistance Among Enterococcus spp. From Dogs Presented at a Veterinary Teaching Hospital, South Africa - Oguttu, James Wabwire; Qekwana, Daniel Nenene; Odoi, Agricola (Frontiers in Veterinary Science, 2021)
Background: While surveillance of antimicrobial drug resistance is ongoing in human medicine in South Africa, there is no such activity being performed in veterinary medicine. As a result, there is a need to investigate antimicrobial resistance among enterococci isolated from dogs in South Africa to improve understanding of the status of antimicrobial drug resistance given its public and veterinary public health importance. This study investigated antimicrobial resistance and factors associated with resistance profiles of enterococci isolated from dogs presented for veterinary care at a veterinary teaching hospital in South Africa. Methods: In total 102 Enterococcus isolated between 2007 and 2011 by a bacteriology laboratory at a teaching hospital were included in this study. Antimicrobial susceptibility of the isolates was determined against a panel of 18 antimicrobials using the Kirby Bauer disc diffusion technique. Chi-square and Fisher’s exact tests were used to assess simple associations between year, season, breed group, age group, sex, and specimen as covariates and antimicrobial resistance as the outcome. Multivariable logistic models were used to investigate predictors of AMR. Results: All the Enterococcus isolates were resistant to at least one antimicrobial. High proportions of isolates were resistant against lincomycin (93%), kanamycin (87%), orbifloxacin (85%), and aminogycoside-lincosamide (77%). Ninety three percent (93%), 35.3%, and 8.8% of the isolates exhibited multi-drug, extensive-drug and pan-drug resistance, respectively. Only year was significantly (p=0.019) associated with extensive-drug resistance Conclusion: Given the zoonotic potential of Enterococcus spp., the high antimicrobial resistance and Multi-drug resistance observed in this study are a public health concern from one health perspective. The identified resistance to various antimicrobials may be useful in guiding clinicians especially in resource scarce setting where it is not always possible to perform AST when making treatment decisions.